Histories poems - Veric, Charlie S. (Charlie Samuya) (Ateneo de Manila University Press, 2015)
"At once memoir, theory, verse, Histories by Charlie Samuya Veric reveals a sensibility remarkable for its breadth and ambition. This is poetry of great integrity, unburdened by the conventions of writing programs, workshops, contests, coteries. Above all, it is poetry at its most private, probing deep into the lyric imagination of an observer who speaks in a genial tongue. Here is poetry as the achievement of personal autonomy in which the fragments of lived life are hauntingly illuminated."--Cover.